Multi-scale interaction of particulate flow and the artery wall. - Halliday, I; Atherton, M; Care, C; Collins, M; Evans, D; Evans, P; Hose, DR; Khir, A; König, C; Krams, R; Lawford, P; Lishchuk, S; et al. (2011)
We discuss, from the perspective of basic science, the physical and biological processes which underlie atherosclerotic (plaque) initiation at the vascular endothelium, identifying the widely separated spatial and temporal scales which participate. We draw on current, related models of vessel wall evolution, paying particular attention to the role of particulate flow (blood is not a continuum fluid), and proceed to propose, then validate all the key components in a multiply-coupled, multi-scale modeling strategy (in qualitative terms only, note). Eventually, this strategy should lead to a quantitative, patient-specific understanding of the coupling between particulate flow and the endothelial state.